Gambaran perubahan berat badan pada akseptor KB suntik 3 bulan di Puskesmas Rawat Inap Kemiling Kota Bandar Lampung - Nurhayati, Nurhayati; Fitri, Feni Elda; Wulan, Sarinah Sri; Rahayu, Ajeng (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: 3-month birth control injection is a contraceptive device containing hormones such as DMPA (Depo medroxyprogesterone acetate) and NET-EN which are injected intramuscularly (IM) into the buttocks area of ​​women once every 3 months. The most common side effect felt by users of 3-month birth control injections is weight changes. Weight changes can be influenced by the presence of the hormone Depo Medroxyprogesterone acetate (DMPA) which can stimulate the appetite control center in the hypothalamus, causing acceptors to experience an increase in appetite from usual. Purpose: To determine the description of weight changes in acceptors of 3-month birth control injections. Method: Descriptive research to see the description of weight changes for users of 3-month birth control injections. The description of weight changes is not by comparing or connecting the independent variables with other factors. The population is users of 3-month birth control injections at the Kemiling Inpatient Health Center, Bandar Lampung and using the total sampling technique, 30 people were selected as respondents. The inclusion criteria were willingness to be a respondent, using 3-monthly contraceptive injections, and duration of contraceptive injection use ≥1 year. Results: Most of the respondents' employment status was as housewives, namely 28 (93.4%). All respondents had a regular diet, namely 30 (100.0%). The majority of respondents' blood pressure was in Pre-hypertension 120-139 mmHg, namely 14 (46.7%). Most respondents experienced changes in weight gain, namely 29 (96.7%). The majority of respondents had used contraceptive injections for 4-6 years, namely 15 (50.0%) and the history of the type of contraception used by respondents previously was mostly contraceptive injections, namely 26 (86.6%). Conclusion: Weight gain for users of 3-month contraceptive injections is influenced by age, employment status, duration of contraceptive injection use, and regularity of diet. The more dominant factors influencing weight gain for users of 3-month contraceptive injections are employment status and regularity of diet. Suggestion: To be an additional reference for the development of knowledge and increasing public understanding about the relationship between types of contraception and the description of weight changes in 3-month injectable contraceptive acceptors so that they can maintain a healthy quality of life by doing physical activities, improving diet, and choosing the right contraception. Keywords: 3-month injectable contraceptives; KB acceptors; Weight changes Pendahuluan: Suntik KB 3 bulan yaitu alat kontrasepsi yang berisikan hormonal seperti DMPA (Depo medroxyprogesterone acetat) dan NET-EN yang disuntikan secara intramuscular (IM) pada area bokong wanita dalam 3 bulan sekali. Efek samping terbanyak yang dirasakan dari akseptor KB suntik 3 bulan yaitu, perubahan berat badan. Perubahan berat badan dapat dipengaruhi karena adanya hormon Depo Medroxyprogesterone acetat (DMPA) yang dapat merangsang pusat pengendalian nafsu makan di hipothalamus sehingga menyebabkan akseptor mengalami peningkatan nafsu makan dari biasanya. Tujuan: Untuk mengetahui gambaran perubahan berat badan pada akseptor KB suntuk 3 bulan. Metode: Penelitian deskriptif untuk melihat gambaran perubahan berat badan bagi pengguna KB suntik 3 bulan. Gambaran perubahan berat badan tidak dengan membandingkan atau menghubungkan variable independennya dengan faktor lain. Populasinya adalah pengguna KB suntik 3 bulan di Puskesmas Rawat Inap Kemiling Bandar Lampung dan dengan teknik total sampling mendapatkan sebanyak 30 orang menjadi responden. Kriteria inklusinya adalah bersedia menjadi responden, menggunakan KB suntik 3 bulan, dan lama pemakaian KB suntik ≥1 tahun Hasil: Sebagian besar status pekerjaan responden adalah sebagai ibu rumah tangga yaitu sebanyak 28 (93.4%). Seluruh responden memiliki pola makan yang teratur yaitu sebanyak 30 (100.0%) Mayoritas tekanan darah responden pada Pre-hipertensi 120-139 mmHg yaitu sebanyak 14 (46.7%). Sebagian besar responden mengalami perubahan kenaikan berat badan yaitu sebanyak 29 (96.7%). Mayoritas responden sudah menggunakan KB suntik selama 4-6 tahun yaitu sebanyak 15 (50.0%) dan riwayat jenis KB yang digunakan responden sebelumnya adalah sebagian besar adalah KB suntik yaitu sebanyak 26 (86.6%). Simpulan: Kenaikan berat badan bagi pengguna KB suntik 3 bulan dipengaruhi oleh faktor usia, status pekerjaan, lamanya penggunaan KB suntik, dan keteraturan pola makan. Faktor yang lebih dominan mempengaruhi kenaikan berat badan bagi akseptor KB suntik 3 bulan adalah status pekerjaan dan keteraturan pola makan. Saran: Menjadi referensi tambahan untuk pengembangan pengetahuan dan peningkatan pemahaman kepada masyarakat tentang hubungan jenis kontrasepsi dan gambaran perubahan berat badan pada akseptor KB suntik 3 bulan sehingga dapat menjaga kualitas hidup sehat dengan melakukan aktifitas fisik, memperbaiki pola makan, dan memilih kontrasepsi yang tepat.